Analysis of marketing activities of an enterprise and ways to improve them on the example of the Logfort transport company - D. V. Koplik (Вестник университета)
The article analyzes marketing activities of an enterprise on the example of the Logfort transport company and proposes ways to improve such activities. The relevance of the topic is high, since amidst anti-Russian sanctions and due to the challenges of the post-COVID period, various industries of the Russian economy, such as the transport industry, have been placed in an especially unfavorable economic situation. With regard to companies that do not pay proper attention to marketing today, it has been found that the bankruptcy risk gradually and steadily increases. In this respect, the author stresses the importance of improving marketing activities and uses the example of a particular company to identify the problems that organizations run the risk of facing when carrying out marketing activities. A conclusion suggesting the need to eliminate the identified problems is made, and ways to solve them are proposed. The findings of the study can be applied to improve marketing activities of any company as well as operations in general.